Glycosyltransferase complexes improve glycolipid synthesis - Spessott, Waldo Andrés (2012)
The synthesis of gangliosides GM3 and GD3 is carried out by the successive addition of sialic acid residues on lactosylceramide (LacCer) by the Golgi located sialyltransferases Sial-T1 and Sial-T2, respectively. CHO-K1 cells lack Sial-T2 and only express GM3. Here we show that the activity of Sial-T1 was near 2.5-fold higher in homogenates of CHO-K1 cells transfected to express Sial-T2 (CHO-K1 Sial-T2) than in untransfected cells. The appearance of Sial-T1 enzyme or gene transcription activators or the stabilization of the Sial-T1 protein were discarded as possible causes of the activation. Sial-T2 lacking the catalytic domain failed to promote Sial-T1 activation. Since Gal-T1, Sial-T1 and Sial-T2 form a multienzyme complex, we propose that transformation of formed GM3 into GD3 and GT3 by Sial-T2 in the complex leaves Sial-T1 unoccupied, enabled for new rounds of LacCer utilization, which results in its apparent activation. Crown Copyright © 2012 Published by Elsevier B.V. on behalf of Federation of European Biochemical society. All rights reserved.